Effects of Human Resource Management on Health Tourism in Thermal Centers in Kosovo Case study: Centre’s of Thermal Tourism in Kosovo: Array - Tahiri, Alberta; Kovaçi, Idriz; Thaqi, Agim; Goga, Arta Jashari (Acta Universitatis Danubius. Œconomica, 2020)
Proper management of thermal centres through human resource management has enabled the health tourism in Kosovo to be successful. Through training of staff and human resources, communication and working climate, job evaluation and employee motivation, we have achieved positive and satisfying effects on health tourism in Kosovo. This is evidenced by this research, where we find that the key factors that influence high standards are employee training, evaluation, communication and motivation. This was accomplished through the participation of a total of 4 thermal centres in Kosovo, of which there are 12 managers and 75 employees, while the analysis was performed through SPSS (version 25), and the analysis method was regression. On the basis of the results we see that proper human resource management leads to overall sustainability and satisfaction of employees in these enterprises and their performance at work (p value = .000 <1%).